Orientalism in Louis XIV's France - Dew, Nicholas (Oxford University Press, 2009)
This title presents a history of Oriental studies in 17th century France, revealing the prominence within the intellectual culture of the period that was given to studies of Arabic, Persian, Turkish, and Chinese texts, as well as writings on Mughal India.
10.1093/acprof:oso/9780199234844.001.0001
Keywords: Herbelot; Barthélemy d'; Thévenot; Melchisédec; Bernier; François; Herbelot; Thévenot; Bernier; Orientalism